The impact of horizontal and vertical FDI on labor demand for different skill groups - Anselm Mattes (Institut für Angewandte Wirtschaftsforschung (IAW), 2009)
This paper analyzes the determinants and effects of firm-level FDI flows on the basis of German micro-level data. Concering the determinants of FDI, I differentiate between different target regions and motivations for FDI (market seeking/horizontal FDI versus cost reducing/vertical FDI). The main result is that most firms engage in FDI because of market access. Further, I focus on the employment effects of direct investment projects abroad. From a theoretical point of view, the effects of FDI flows on labor demand at the firm level are uncertain. Therefore, this paper analyzes this question empirically using theory-based labor demand regressions and and an econometric framework based on the generalized method of moments (GMM). As a main result I find that there is no negative effect of firm-level FDI flows on employment. Positive effects seem plausible in many specification. Further, theory and anecdotal evidence suggest that unskilled workers are acted worse than highly or medium-skilled employees. Hence, the analysis distinguishes between different skill groups. Again, I cannot find negative effects of firm-level FDI flows on any skill group.
Keywords: F16; F23; J23; 330; FDI; horizontal FDI; vertical FDI; labor demand; skill groups; GMM; Direktinvestition; Internationale Markteintrittsstrategie; Arbeitsnachfrage; Qualifikation; Beschäftigungseffekt; Schätzung; Deutschland